A survey on the effects of metabolic syndrome on the periodontal indices of hemodialysis patients - Mohammad Tavakoli; Mozhgan Izadi; Jaber Yaghini; Abdolah Rastegari; Ahmad Moghareh Abed (Wolters Kluwer Medknow Publications, 2016)
Background: The metabolic syndrome and periodontitis coincide with systemic inflammation and glucose tolerance disorder, which indicate the common pathophysiologic pathway of these diseases. The main goal of this study was to determine the effects of the metabolic syndrome on the periodontal indices of hemodialysis (HD) patient. Materials and Methods: In this descriptive-analytical study, 75 persons were selected by the simple method, 50 of them were HD patients, and 25 of them were healthy people. They were divided into three groups each of which included 25 persons. The periodontal conditions of the selected persons were determined by radiography, gingival index, probing pocket depth, and bleeding index. Then, the periodontal indices of the patients suffering from metabolic syndrome and the persons not affected by metabolic syndrome were compared. At the end, the data were analyzed by SPSS software (version 20) using Mann-Whitney and Kruskal-Wallis tests at the meaningful level of α = 0.05. Since the condition of the unilateral variance test could not be provided for this study, the Kruskal-Wallis test was used. To complete the test, the Mann-Whitney test was used in the binary form among the groups being studied. Results: The obtained results showed a meaningful difference among the groups under study (P < 0.001). The results of the test showed a meaningful difference among the obtained indices of the groups being studied in the binary form (P < 0.001) too. Conclusion: The results of the present study revealed when the severity of chronic systemic disease increased the health of the periodontal tissues would decrease.